Citizenship Education and Child Participation: Reflections for Initial Teacher Training in Chile - Torres-Valderrama, Sebastián (2025)
Educational space has been fundamental to promoting knowledge, skills, and citizenship attitudes in children and young people at school. In this sense, Citizenship Education has acquired importance in the pedagogical field since its objectives are to defend, promote, and practice democracy in school contexts. Therefore, the purpose of this essay is to reflect on the implications of Law 20.911 for Initial Teacher Education in Chile. First, the purposes of Citizenship Education are addressed, then the curricular evolution at the local level is contextualized, to end with the results of research that have had positive effects on initial teacher education. It is concluded that teachers must have solid tools to address citizenship training in schools and that universities have the responsibility to update their curricula to strengthen pedagogical competencies in citizenship.